Two new species of the genus Phlugiolopsis (Tettigoniidae: Meconematinae) and the male description of Phlugiolopsis circolobosis Bian, Shi & Chang, 2013 from Yunnan, China - Zheng, Mengjia; Shi, Fuming; Chang, Yanlin (Zootaxa, 2023)
This paper reports two new species of the genus Phlugiolopsis from Yunnan, China, i.e. Phlugiolopsis furcicaudis sp. nov. and Phlugiolopsis breviproceris sp. nov., and describes the male of Phlugiolopsis circolobosis Bian, Shi & Chang, 2013 for the first time. Examined specimens are deposited in the Museum of Hebei University.